α-Arylation of Amides from α-Halo Amides Using Metal-Catalyzed Cross-Coupling Reactions - Barde, E.; Guérinot, A.; Cossy, J. (Synthesis, 2019)
Metal-catalyzed α-arylation of amides from α-halo amides with organometallic reagents is reviewed. The article includes Suzuki–Miyaura, Kumada–Corriu, Negishi, and Hiyama cross-coupling reactions.1 Introduction2 Suzuki–Miyaura Cross-Coupling2.1 Palladium Catalysis2.2 Nickel Catalysis3 Kumada–Corriu Cross-Coupling3.1 Nickel Catalysis3.2 Iron Catalysis3.3 Cobalt Catalysis4 Negishi Cross-Coupling5 Hiyama Cross-Coupling6 Conclusion
Keywords: amide; arylation; cross-coupling; metal catalysis